A Systemic Literature Review on Ecological Approach in Language Teaching; State of the Art and Future Direction - Alfiatus Syarofah; mamluatul hasanah; Muassomah; Uril Bahruddin; Lateef Onireti Ibraheem (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2024)
This study explored how to use ecological approach to provide more contextual and relevant learning experiences for students. The use of an ecological approach in language learning is systematically reviewed in this work using a comprehensive literature review methodology. The review process is methodologically designed as a result of these processes adhering to a clear and transparent framework. The 35 articles found are then selected by inclusion and exclusion categories to produce 7 articles for analysis according to the literature review focusing on language learning both internally and externally. Key findings from the selected studies are examined to acquire a thorough grasp of the impact of ecological techniques in language learning environments. The findings of the analysis demonstrate that an ecological approach to language acquisition has the potential to significantly improve students' learning experiences by using an inclusive, responsive, and holistic approach.